Integrated Service Delivery Analysis of Public Service Malls in Pemalang Regency - Sunarya, Amud; Milwan, Milwan; Sari, Jayanti Armida; Yunus, Norhanishah Mohamad (Universitas Teuku Umar, 2025)
This study aims to assess community satisfaction with services provided by the Public Service Mall (MPP) in Pemalang Regency and identify its service elements' strengths and weaknesses. Using a quantitative approach, data was collected from 247 respondents selected through proportional simple random sampling, based on a population of 646 service users. The research instrument was developed by the Indonesian Ministerial Regulation No. 14 of 2017, which outlines nine key elements for measuring the Community Satisfaction Index (IKM). The data were analyzed using univariate and bivariate methods. The findings show that the overall IKM score was 88.18, indicating good service quality. While most service elements were rated in category B (good), two elements—service requirements and complaint handling—received the lowest scores (3.41), suggesting areas needing improvement. Conversely, service tariffs and infrastructure scored highest, with 3.94 and 3.75, respectively. The study highlights the need for clearer information dissemination, simplified procedures, and more responsive complaint mechanisms. It also recommends the integration of digital platforms to enhance accessibility and efficiency. Continuous evaluation and stakeholder engagement are essential to ensure sustainable improvements in public service delivery and community satisfaction at the MPP.